The Inventory of Communication Patterns For Adolescents (ICPA) - West, Lloyd W.; Altmann, Harold A. (Canadian Journal of Counselling and Psychotherapy, 2011)
The early development of instruments to measure self-disclosure and the conceptual confusion related to that construct are briefly discussed. The relevance of interpersonal communication to the growing field of social support and the need for improved procedures to map communication patterns are noted. A revised edition of the Self-Disclosure Inventory for Adolescents (SDIA), which has been renamed the Inventory of Communication Patterns for Adolescents (ICPA), is presented and its psychometric properties are described. Several counselling applications of the ICPA are presented and a rather comprehensive research agenda is suggested.